Atomistic modelling of actinide oxides for nuclear fuel applications. Issue 2 (21st December 2012) - Walker, Scott R.; Jackson, Robert A.; Read, Mark S. D.; Stanek, Christopher R.; Nikl, Martin; Kovács, László; Greulich‐Weber, Siegmund
Abstract Atomistic computer simulations were performed for the actinide oxides (UO2, PuO2 and MOX) in the temperature range 300 K‐2000 K, in order to elucidate the physical and defect properties of these nuclear fuel materials. Parameterised cation‐anion Buckingham potentials, coupled to a standard Coulomb function, were used to describe the short range and long range interatomic interactions respectively. Mott‐Littleton methodology was employed for accurate defect modelling and to calculate intrinsic defect formation energies. This paper summarises the key findings of a bulk study into these materials and extends this briefly to consider surface effects and morphologies. In addition to highlighting the thermodynamic stability of aggregated defects over isolated point defects, it is shown that the empirical potentials themselves are thermally stable beyond the standard centreline temperatures experienced within a Light Water Reactor (LWR). Finally, minimum energy pathways (MEP) for oxygen migration in UO2 have been investigated, indicating that at least one of the mechanisms, the <110> vacancy migration, is non‐linear. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)